UZBEKISTAN’S WELLNESS TOURISM: OPPORTUNITIES FOR INTERNATIONAL INVESTORS AND PARTNERS - Kudratov Mirjalol Khurshid ugli (TADQIQOTLAR, 2025)
Abstract Central Asian Uzbekistan presents growing potential as a destination for wellness tourism because of its diverse cultural traditions and magnificent scenery. International investors and partners can establish business opportunities in Uzbekistan’s wealth sector development by addressing this piece. Through its resources and ancient landmarks plus state backing Uzbekistan can transform into an international wellness tourism hot spot. The ongoing research unveils the main growth factors alongside strategic advice and market barriers for investment development in this expanding segment of the Tourism industry (Global Wellness Institute, 2023; Uzbekistan Tourism Portal, 2025).